Ends and Means of Knowledge Management: Tacit Knowledge to Explicit Knowledge Conversion - Evgeny E. Zhernov (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки, 2023)
The author interprets conversion of tacit knowledge into explicit knowledge as means-end of knowledge management. The subject of the article is tacit knowledge owned by an employee. The purpose is to reveal the reason for the conversion of non-formalized knowledge of employees to formalized knowledge of a firm. For the knowledge-based production, it is not necessary to formalize all knowledge. The conversion of non-formalized knowledge of employees to formalized knowledge of the organization is one of the functional goals of the firm owner, necessary to obtain stable profit without the direct participation of employees, as well as an end in itself for knowledge managers. The study can serve as a starting point for continuing scientific research in the field of tacit knowledge and as theoretical basis for the development of practical measures for using the knowledge of employees with due respect to their legitimate interests and rights.